PENERAPAN METODE BERMAIN UNTUK MENINGKATKAN HASIL BELAJAR PADA ASPEK MINDFUL LEARNING PASSING BAWAH BOLA VOLI PADA SISWA KELAS X FASE E - Kurniawati, Ananda Rizky; Teguh Hari Wiguno, Lokananta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effectiveness of a play-based learning method in enhancing student learning outcomes on the mindful learning dimension of volleyball underhand passing among Class X Phase E students at SMAN 8 Malang. A Classroom Action Research (CAR) design was adopted, structured across two cycles with two meetings per cycle, involving 34 students of class X-9 as participants. Data were collected through questionnaires and observational instruments covering five mindful learning indicators: awareness, concentration, process awareness, open-mindedness, and reflection. Descriptive quantitative analysis with percentage calculation was employed. Baseline measurement yielded 48% (very poor category). Cycle 1 progressed from 65% (fairly good) at meeting 1 to 74% (fairly good) at meeting 2. Cycle 2 recorded 82% (good) at meeting 3 and 88% (good) at meeting 4. The findings confirm that play-based instruction substantially promotes students' mindful learning in volleyball underhand passing.